Efektivitas Pemanfaatan Waktu Belajar Terhadap Peningkatan Hasil Belajar Mahasiswa Jurusan Pendidikan Teknik Bangunan Fakultas Teknik Unima - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to determine the functional relationship between the implementation of the use of study time on student learning achievement. The subjects of this research were students majoring in building engineering education. The benefits of this research are: 1. It can be used as input for students in improving their efforts, to develop the effectiveness of using study time to improve student learning outcomes. 2. Can detect the extent of the relationship between the level of discipline in the use of time, the distribution of study time and the use of student free time for study. 3. Can be used as empirical data to develop the teaching and learning process in lectures. 4. Can be used as reference material for conducting research in the future. The indicators are discipline in the use of time, distribution of study time, use of free time and average grades for the even semester of 2023/2024. Based on the results of this research, it is recommended that students use their study time as well as possible to try to repeat the lessons they have just learned/given by the lecturer, use their free time to study, then their learning achievements will be more successful.